NEW APPROACHES FOR TEACHING THE STUDENTS IN MODERN CONDITIONS - Khalibekova Amangul; Jahonova Marjona, Doniyorova Guzal, Eshmurodova Dinora, Suyunova Sevara, (EPRA International Journal of Research and Development (IJRD), 2023)
This research paper investigates the study of various subjects, more and more attention for teaching. This led to the need for teachers to individually study and put into practice various electronic learning services. It also analyzes the importance of development of teaching students in modern conditions. This investigation was conducted by using various electronic distance learning services showed the presence of a large number of existing platforms for different target audiences (Moodle, ISPRING, Google, etc.). The study revealed that the development of they must be more informed and disciplined, learn to assimilate and generalize the information received from various sources independently (video lectures, books, teaching aids, recommendations, various information sites on the subject under the study, etc.)